Inequality of Opportunity and Economic Development - Ferreira, Francisco H.G.; Walton, Michael (World Bank, Washington, DC, 2012)
Just as equality of opportunity becomes an increasingly prominent concept in normative economics, the authors argue that it is also a relevant concept for positive models of the links between distribution and aggregate efficiency. Persuasive microeconomic evidence suggests that inequalities in wealth, power, and status have efficiency costs. These variables capture different aspects of people's opportunity sets, for which observed income may be a poor proxy. One implication is that the cross-country literature on income inequality and growth may have been barking up the wrong tree, and that alternative measures of the relevant distributions are needed. The authors review some of the detailed microeconomic evidence, and then suggest three research areas where further work is needed.